Formation of Social Values in Students Through Adolescent Red Cross (PMR) Extracurricularies at SMAN 1 Anjir Muara - Ersis Warmansyah Abbas; Jumriani Jumriani; M. Ridha Ilhami; Raihanah Sari; Wiwi Musriana (The Innovation of Social Studies Journal, 2024)
There are many cases related to the lack of awareness of social values that exist in students such as the case of sexual abuse of a teenager in Alalak Barito Kuala, South Kalimantan minors. The teenager was 15 years old and the victim was 13 years old. The perpetrator and victim were friends with each other and went to school in the same place, then their residences were also not far apart. The motive for the perpetrator to do this is not clear why. But when it was revealed, they were alone in the perpetrator's house. This example can be seen that the lack of social values that exist in students until they make deviations. This study aims to: 1) Describe the extracurricular activities of PMR SMAN 1 Anjir Muara, Barito Kuala Regency. 2) Social values in PMR extracurricular activities at SMAN 1 Anjir Muara, Barito Kuala Regency. In this study, qualitative research methods were used with data collection techniques in the form of observation, interviews and documentation. The research instrument is the researcher himself who provides observation, observation and interview guidelines. The data analysis techniques used are data reduction, data presentation and conclusions. Data validity checking using source, technique and time triangulation. The results of research on the formation of social values in students through PMR activities at SMAN 1 Anjir Muara are supporting facilities and infrastructure, PMR activities at SMAN 1 Anjir Muara include indoor and outdoor activities. So it can be concluded that the activities of PMR SMAN 1 Anjir Muara have social values in these activities, namely cooperation, love to play, love to love, harmony, like to give advice, and care about the fate of others.